2020
DOI: 10.1108/oir-06-2019-0203
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and barriers to MOOC adoption: perspectives from adopters and non-adopters

Abstract: PurposeDespite the advantages of MOOCs (Massive Online Open Courses), the adoption rate is still low, especially in less developed countries. The present study aims to investigate the drivers and barriers faced by adopters and non-adopters of MOOCs, and examine how these factors influence the intention of MOOC adoption.Design/methodology/approachA survey questionnaire was developed to measure how the identified factors may impact adopters and non-adopters' intention of using MOOCs. Through both offline and onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Indeed, online educational videos can be as viable means to disseminate educational instructions and in the process empowering learners to take charge of their learning (Lee et al, 2017). Last, face‐to‐face sections in blended learning could provide students with opportunities to interact with peers and get feedback from instructors after online learning (Ma & Lee, 2020). Past works have emphasized the importance of social presence of peer learners and instructor in the face‐to‐face learning as it enables interactivity during the learning process (Griffiths et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, online educational videos can be as viable means to disseminate educational instructions and in the process empowering learners to take charge of their learning (Lee et al, 2017). Last, face‐to‐face sections in blended learning could provide students with opportunities to interact with peers and get feedback from instructors after online learning (Ma & Lee, 2020). Past works have emphasized the importance of social presence of peer learners and instructor in the face‐to‐face learning as it enables interactivity during the learning process (Griffiths et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, negative consequences include unsatisfactory learning outcome due to the lack of social interaction and self‐regulation (Koutropoulos et al, 2012). At a broader level, social issues such as the widening of the digital divide may surface as economically disadvantaged students may not have access to the technology or technological infrastructure to access the online resources (Ma & Lee, 2020). Thus, the educational transformation driven by the pandemic underscores that workable approaches to teaching and learning are needed in the new normal after the pandemic (Govindarajan & Srivastava, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm has caused an influx of research on MOOCs, with over two thirds of this evidence base dedicated to understanding learner behaviour and MOOC adoption (Meet & Kala, 2021 ). Successful MOOC adoption has been linked to leaners’ perceived usefulness and performance-to-cost value, while barriers have been identified as insufficient time, poor instruction, difficulty with subject matter, lack of internet accessibility and under challenging assignments (Gütl et al, 2014 ; Ma & Lee, 2019 , 2020 ). Learner self-regulation has been identified as both an enabler and barrier to MOOC adoption, depending on the learner (Ma & Lee, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to switching costs, such learning costs also involve the pattern of habitual behavior and emotional cost of an individual. Ma and Lee (2020) examined customers who used MOOCs in the least developed countries in Asia and found that traditional teaching and peer influence were the main obstacles to MOOC usage. Thus, the drive for customers, or “residents”, to stay in, or leave, their original place of residence can be summarized as mooring, an influential concept on migration behavior ( Moon, 1995 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%